Scheduling multi-resource satellites using genetic algorithms and permutation based representations - Quevedo de Carvalho, O., author; Whitley, D., author; Shetty, V., author; Jampathom, P., author; Roberts, M., author; ACM, publisher (Colorado State University. Libraries, 2023)
The U.S. Navy currently deploys Genetic Algorithms to schedule multi-resource satellites. We document this real-world application and also introduce a new synthetic test problem generator. A permutation is used as the representation. A greedy scheduler then converts the permutation into a schedule which can be displayed as a Gantt chart. Surprisingly, there have been few careful comparisons of standard generational Genetic Algorithms and Steady State Genetic Algorithms for these types of problems. In addition, this paper compares different crossover operators for the multi-resource satellite scheduling problem. Finally, we look at two ways of mapping the permutation to a schedule in the form of a Gantt chart. One method gives priority to reducing conflicts, while the other gives priority to reducing overlaps of conflicting tasks. This can produce very different results, even when the evaluation function stays exactly the same.
Keywords: scheduling; steady state genetic algorithm; order crossover